Empathy: The Role of Expectations. (April 2018) - Trapp, Sabrina; Schütz-Bosbach, Simone; Bar, Moshe
To what extent can we feel what someone else feels? Data from neuroscience suggest that empathy is supported by a simulation process, namely the neural activation of the same or similar regions that subserve the representation of specific states in the observer. However, expectations significantly modulate sensory input, including affective information. For example, expecting painful stimulation can decrease the neural signal and the subjective experience thereof. For an accurate representation of the other person's state, such top-down processes would have to be simulated as well. However, this is only partly possible, because expectations are usually acquired by learning. Therefore, it is important to be aware of possible misleading simulations that lead to misinterpretations of someone's state.